Diffractive dijet production at sqrt[s] = 630 and 1800 GeV at the Fermilab Tevatron. - Acosta, D; Affolder, T; Akimoto, H; Albrow, MG; Amaral, P; Ambrose, D; Amidei, D; Anikeev, K; Antos, J; Apollinari, G; Arisawa, T; Artikov, A; et al. (2002)
We report a measurement of the diffractive structure function F(D)(jj) of the antiproton obtained from a study of dijet events produced in association with a leading antiproton in pp collisions at sqrt[s] = 630 GeV at the Fermilab Tevatron. The ratio of F(D)(jj) at sqrt[s] = 630 GeV to F(D)(jj) obtained from a similar measurement at sqrt[s] = 1800 GeV is compared with expectations from QCD factorization and other theoretical predictions. We also report a measurement of the xi ( x-Pomeron) and beta ( x of parton in Pomeron) dependence of F(D)(jj) at sqrt[s] = 1800 GeV. In the region 0.035